Kampus sebagai Ruang Damai: Implementasi Toleransi Beragama di UIN K.H. Abdurrahman Wahid Pekalongan - Faiz Zaidan Saputra; Muhamad Masrur; Syihabud Din; Desvita Ina Amelia; Layla Fayza Aryanti (Moderasi : Journal of Islamic Studies, 2026)
This article analyses strategies for implementing tolerance values in constructing a peaceful campus at UIN K.H. Abdurrahman Wahid Pekalongan. The study employs a qualitative library-research and documentary-analysis approach, using official institutional publications, policy documents on religious moderation, and recent scholarly literature on religious tolerance, interfaith dialogue, higher education, and persuasive communication. The analysis is organised through the framework of religious moderation and the persuasive communication strategy of Melvin L. DeFleur and Sandra J. Ball-Rokeach, namely psychodynamic, sociocultural, and meaning-construction strategies. The findings show that tolerance values at UIN K.H. Abdurrahman Wahid Pekalongan are implemented through four mutually reinforcing pathways: curricular integration of religious moderation, academic and non-academic programmes, participatory and inclusive interfaith dialogue, and persuasive communication practices that cultivate empathy, institutional norms, and shared meanings. The study argues that the peaceful-campus model is not merely a moral appeal, but an institutional ecosystem that links policy, curriculum, student activities, community engagement, and digital literacy. This article contributes to Islamic studies and religious moderation scholarship by demonstrating how tolerance can be translated into educational governance and social practice in an Islamic higher education institution without reducing religious identity or simplifying Indonesia’s plural social context.